Nivolumab exposure-response analysis for adjuvant treatment of melanoma supporting a change in posology - Kinjal Sanghavi; Pradeep Vuppala; Vijay Ivaturi; Lora Hamuro; Amit Roy; Satyendra Suryawanshi (Wiley, 2021)
Abstract Nivolumab monotherapy is approved as adjuvant treatment for melanoma based on results from the pivotal CheckMate 238 trial. We present a model‐based, benefit-risk assessment of nivolumab in adjuvant melanoma supporting a posology change from a weight‐based to a less frequent, flat‐dosing regimen. The exposure-response (E-R) relationship for efficacy was evaluated using recurrence‐free survival (RFS) and distant metastasis‐free survival (DMFS) end points from the CheckMate 238 trial. The E-R for safety was evaluated using data from 14 studies across a broad range of doses in several tumor types using grade 3+ adverse event (AE) and grade 2+ immune‐mediated AE (IMAE) end points. Nivolumab trough exposures were not significant predictors of RFS or DMFS. Covariates significantly associated with increased risk of disease recurrence or death were programmed death ligand 1 (PD‐L1; less than 5% cutoff), lower baseline lactate dehydrogenase, and higher age. Covariates associated with increased risk of distant metastasis or death were PD‐L1 (less than 5% cutoff) and higher age. Higher nivolumab maximum concentration after first dose (Cmax1) was significantly associated with grade 2+ IMAEs, but not grade 3+ AEs. The risk of grade 3+ AEs was significantly lower in adjuvant versus advanced melanoma. Eastern Cooperative Oncology Group Performance Status higher than zero was associated with higher incidences of grade 2+ IMAEs and grade 3+ AEs. Female patients had significantly higher incidences of grade 2+ IMAEs than male patients. Nivolumab monotherapy in adjuvant melanoma demonstrated a relatively flat E-R relationship over the range of exposures produced by 3 mg/kg every 2 weeks and predicted a comparable benefit-risk profile to flat‐dosing regimens.